Real-world incidence of monofocal toric intraocular lens repositioning: analysis of the American Academy of Ophthalmology IRIS Registry. Issue 3 (March 2022) - Kramer, Brent A.; Berdahl, John; Gu, Xiaolin; Merchea, Mohinder
Abstract : Analysis of 6482 eyes in the American Academy of Ophthalmology IRIS Registry found that the 12-month repositioning rate was higher after implantation of TECNIS than after AcrySof monofocal toric IOLs. Abstract : Purpose: To determine the 12-month incidence of reoperation to realign 2 commercially available types of implanted monofocal toric acrylic intraocular lenses (IOLs). Setting: American Academy of Ophthalmology IRIS (Intelligent Research in Sight) Registry. Design: Registry retrospective study. Methods: Eyes that underwent cataract extraction and were implanted with a TECNIS or AcrySof monofocal toric IOL in 2016 and 2017 were identified. The rate of reoperation for IOL realignment (Current Procedural Terminology code 66825) within 365 days of implantation was determined for each IOL group. Risk factors for repositioning were evaluated using logistic regression modeling. Results: A total of 6482 eyes were implanted with a monofocal toric IOL, including 2013 (31.06%) with a TECNIS and 4469 (68.94%) with an AcrySof IOL. During the first postoperative year, 87 (1.3%) eyes underwent surgical IOL repositioning. The incidence of repositioning was significantly higher ( P < .0001) for TECNIS-implanted (3.1%, 62/2013) than for AcrySof-implanted (0.6%, 25/4469) eyes (odds ratio [OR] 5.6; 95% CI, 3.5-8.9). Younger age (OR 0.76; 95% CI, 0.67-0.86 per 5-year increase) was associated with a higher risk for IOL repositioning. Conclusions: Real-world analysis of U.S. patients in the IRIS Registry revealed that the rate of surgical IOL repositioning was 5 times higher in eyes implanted with TECNIS than with AcrySof monofocal toric IOLs for astigmatic correction at the time of cataract surgery. These findings should be considered when selecting a toric IOL for correction of astigmatism in cataract patients, particularly in younger patients with a higher risk for misalignment requiring repositioning.